KAPASITAS PEREMPUAN TANI UNTUK MEWUJUDKAN KETAHANAN PANGAN RUMAH TANGGA DALAM MENGHADAPI ERA GLOBALISASI DI KOTA PEKANBARU - Penti Suryani; Ahmad Darmawi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2016)
This study aims to determine 1) the condition of household food security, 2) the factors that affect the capacity of women farmers in food consumption in order to achieve food security at the household level, 3) the factors that affect spending foodstuffs on the level households and 4) the capacity of women farmers to achieve household food security in the era of globalization in the city of Pekanbaru. This study uses a cross-sectional study design, located in four districts in the city of Pekanbaru namely District Tampan, District Marpoyan Damai, District and Sub-district Rumbai and Rumbai Pesisir. Primary data was collected using a questionnaire which was distributed to 100 respondents of women farmers selected by simple random sampling. Factors that affect the capacity of women farmers in achieving food security household level are: income, education and nutrition knowledge of women farmers. Factors that affect spending foodstuffs at the household level women farmers in the city of Pekanbaru is the price of rice, household income, number of household members and the level of education. Capacity of women farmers in food processing is still at the low level. Threats of globalization on food security in Pekanbaru city can be resolved by the farmer community empowerment program. Empowerment of women farmers not only to protect the rice trade, but also to uplift the lives of women farmers through programs that improve local agricultural businesses